Pembuatan Website Kumpulan Berita Hoax Untuk Menjaga Kualitas Pesan Pada Ruang Publik - Subarisman, Subarisman; Ekaputra, Mohammad Zhofir (UNIVED Press, 2018)
The rapid development of technology has resulted in the birth of various new media (New Media) based on the Internet. New media such as websites and social media are increasingly emerging. New Media should be a positive thing, many traditional media are flocking to create new media or change their media to website-based online media. This makes it easier for people to search for information anytime, anywhere, without limitations on time and space. Online media news can spread quickly through social media and also through instant messaging services (messenger). New Media also changes readers who previously could only enjoy news presentations, now they can collaborate or even create media. This becomes a problem when everyone can create media and convey information through their media. The message or information conveyed is sometimes not in accordance with the truth or is intentionally created and conveyed fake news which is usually called Hoax. Hoaxes are even produced deliberately for the benefit of certain groups or people. Hoax reporting makes the media a public space polluted or contaminated. Habermas calls this reformation, namely that the state and certain groups intervene in the public space, in the end it is society that becomes victim of Hoax reporting. To answer this problem, it is necessary to create a media that contains a collection of Hoax news with the aim of being a place to clarify news so that people do not become victims of Hoax news.